Epidemia del virus del mosaico comun del frijol en el Oriente Antioqueno - Tamayo Molano, Pablo J.; Castaño J., Mauricio (1991)
A survey of BCMV in 6 municipalities of western Antioquia, Colombia, confirmed an epidemic in this region. However, planting with virus-free seed and the eradication of BCMV-infected plants during the first 30-40 days after planting were not effective in controlling the disease. Three BCMV-resistant Cargamanto type climbing genotypes were identified (CAR 30, CAR 32, and AND 852).(CIAT)